Tiotropium or salmeterol as add-on therapy to inhaled corticosteroids for patients with moderate symptomatic asthma: two replicate, double-blind, placebo-controlled, parallel-group, active-comparator, randomised trials. Issue 5 (May 2015) - Kerstjens, Huib A M; Casale, Thomas B; Bleecker, Eugene R; Meltzer, Eli O; Pizzichini, Emilio; Schmidt, Olaf; Engel, Michael; Bour, Loek; Verkleij, Cynthia B; Moroni-Zentgraf, Petra; Bateman, Eric D
Summary: Background: In patients with severe asthma, tiotropium improves lung function and exacerbation risk when added to high-dose inhaled corticosteroids plus long-acting β2 agonists. We aimed to assess the safety and efficacy of tiotropium in patients with moderate asthma who were symptomatic despite treatment with medium-dose inhaled corticosteroids. Methods: We did two 24-week, replicate, randomised, double-blind, placebo-controlled, parallel-group, active-comparator trials at 233 sites in 14 countries. Eligible patients were aged 18–75 years with symptomatic asthma and a pre-bronchodilator forced expiratory volume in 1 s (FEV1 ) of 60–90% predicted despite use of medium-dose inhaled corticosteroids, and had never smoked or were ex-smokers for 1 year or more with 10 pack-years or less. Patients were randomly assigned (1:1:1:1), with computer-generated pseudorandom numbers, to receive once-daily tiotropium 5 μg or 2·5 μg, twice-daily salmeterol 50 μg, or placebo, while maintaining inhaled corticosteroids. Patients and study investigators were masked to treatment allocation. Prespecified co-primary endpoints, assessed at week 24 in the full analysis set, were peak FEV1 response, measured within the first 3 h after evening dosing; trough FEV1 response; and responder rate assessed according to the seven-question Asthma Control Questionnaire (ACQ-7). These studies are registered withClinicalTrials.gov, numbersNCT01172808 andNCT01172821 . Findings: Between Aug 24, 2010, and Nov 13, 2012, we randomly assigned 2103 patients to the tiotropium 5 μg group (n=519), the tiotropium 2·5 μg group (n=520), the salmeterol group (n=541), or the placebo group (n=523); 1972 (94%) patients completed the study. Peak and trough FEV1 responses were significantly greater with tiotropium and salmeterol than with placebo and were similar in both studies. With pooled data, difference versus placebo in peak FEV1 was 185 mL (95% CI 146–223) in the tiotropium 5 μg group, 223 mL (185–262) in the tiotropium 2·5 μg group, and 196 mL (158–234) in the salmeterol group (all p<0·0001); difference in trough FEV1 was 146 mL (95% CI 105–188), 180 mL (138–221), and 114 mL (73–155; all p<0·0001), respectively. There were more ACQ-7 responders in the tiotropium 5 μg (OR 1·32, 95% CI 1·02–1·71; p=0·035) and 2·5 μg (1·33, 1·03–1·72; p=0·031) groups, and the salmeterol group (1·46, 1·13–1·89; p=0·0039), than in the placebo group. 48 (2%) of 2100 patients had serious adverse events (tiotropium 5 μg n=11, tiotropium 2·5 μg n=12, salmeterol n=11, placebo n=14). Interpretation: Once-daily tiotropium add-on to medium-dose inhaled corticosteroids reduces airflow obstruction and improves asthma control in patients with moderate symptomatic asthma. Patterns of response with both tiotropium doses were similar to those of salmeterol, and all active compounds had good safety and tolerability. Tiotropium is a safe and effective bronchodilator, and an alternative to salmeterol in this patient population. Funding: Boehringer Ingelheim.